Effective management of miscarriage - Nature Research (16552612) (2016)
Researchers evaluated the use of the drug misoprostol at Women’s Hospital – Hamad Medical Corporation in Qatar in 33 patients with miscarriage. They found that, despite current practices at the hospital varying from World Health Organization recommended dosages and frequencies, the drug’s use was generally successful. Spontaneous miscarriage is a non-induced termination of pregnancy in the first 20 weeks of gestation. Sometimes pregnancy tissues remain in the uterus as a result of a miscarriage and need to be evacuated medically — with drugs that cause the uterus to contract — or surgically. To manage spontaneous miscarriage, the World Health Organization (WHO) recommends the per vaginal use of the drug misoprostol, a prostaglandin that induces cervical stretching and uterine contractions, in varying doses according to the stage of pregnancy. Higher and more frequent doses are recommended the earlier the stage of pregnancy. “This study was the first of its kind in Qatar to evaluate the indications, appropriateness of dosing and outcomes of misprostol when used for medical evacuation of spontaneous miscarriage,” says clinical pharmacist Samah ElSalem from Qatar’s Women’s Hospital. The study found that medical evacuation was successful in more than 60% of cases. It was particularly successful in patients at 10 to 12 weeks (75% success) and 13 to 22 weeks (54% success) of pregnancy, respectively. Four out of five of patients less than nine weeks pregnant required surgical evacuation of remaining uterine tissue following drug treatment. Current practice at the Women’s Hospital was not always found to be in accordance with WHO recommendations, which can be attributed to a lack of comprehensive knowledge about these recommendations, the researchers report. The sale of misoprostol increased exponentially in the Middle East between 2002 and 2007, with retail pharmacy sales rising by 1,022%. In addition to being effective, it is cheaper than other conventional prostaglandins. It is also a much cheaper option than surgical evacuation, which carries around ten times more personnel costs than medical evacuation using misoprostol. “The study results can be used as a starting point for standardizing the practice and dosing regimen of misoprostol at the Women’s Hospital in Doha, Qatar,” says ElSalem. The researchers are currently in the process of conducting further studies on the use of misoprostol for the medical evacuation of spontaneous miscarriages in patients with a previous caesarean section. Other Information Published in: QScience.com Highlights, Published by Nature Research for Hamad bin Khalifa University Press (HBKU Press) License: http://creativecommons.org/licenses/by/4.0